Relationship of response and survival in patients with relapsed and refractory multiple myeloma treated with pomalidomide plus low-dose dexamethasone in the MM-003 trial randomized phase III trial (NIMBUS). Issue 12 (1st December 2016) - Moreau, Philippe; Weisel, Katja C.; Song, Kevin W.; Gibson, Craig J.; Saunders, Owain; Sternas, Lars Axel; Hong, Kevin; Zaki, Mohamed H.; Dimopoulos, Meletios A.
Abstract: Relapsed/refractory multiple myeloma (RRMM) patients have poor overall survival (OS). Pomalidomide plus low-dose dexamethasone (POM + LoDEX) significantly extends OS in RRMM vs. high-dose dexamethasone. Survival of patients with stable disease (SD) was compared to patients with progressive disease (PD) or ≥ partial response (≥PR) at cycles (C) 3, 5, and 7. Among 302 patients randomized to POM + LoDEX, at C3 19.2% achieved ≥ PR, 38.4% SD, and 14.6% PD. Patients with SD at C3 (17.4%) and C5 (13.6%) showed improved responses at C7. Median OS from randomization by response at C3 was 22.4 months for ≥ PR ( n  = 58, HR 0.66; 95% CI 0.40–1.08, p  = 0.0976 vs. SD), 16.2 months for SD ( n  = 116), and 6.3 months for PD ( n  = 44, HR 3.43; 95% CI 2.23–5.27, p  < 0.0001 vs. SD). Similar patterns were observed for C5 and C7. Results show that POM + LoDEX should be a standard treatment after lenalidomide and bortezomib, including in SD patients.